(untitled) (Jurnal Kemanusiaan, 2017)
This empirical study presents the impact of subsidies on the growth of the Malaysian economy by using both the subsidy data to the end user and input subsidies. Econometric analysis shows three important evidences. First, in the short term, the government’s decision to offer subsidies is affected by national output, and vice versa. Second, the findings prove the existence of a two-way relationship between non-subsidy spending and output. Third, non-subsidy expenditure is also influenced by subsidy expenditure and subsidies to consumers in the long run. Finally, there was no significant cointegration between aggregate government spending and output in the long term, which reflects the importance of the role of private sector in fostering the national development. Kajian ini secara empirikal membentangkan kesan subsidi terhadap pertumbuhan ekonomi Malaysia dengan menggunakan kedua-dua data subsidi kepada pengguna akhir dan subsidi input. Analisis ekonometrik menunjukkan tiga bukti yang penting. Pertama, dalam jangka pendek, keputusan kerajaan untuk menawarkan subsidi dipengaruhi oleh output negara, dan sebaliknya. Kedua, dapatan membuktikan kewujudan hubungan dua arah antara belanja bukan subsidi dan output. Ketiga, belanja bukan subsidi turut dipengaruhi oleh belanja subsidi dan subsidi kepada pengguna dalam jangka panjang. Akhir sekali, tidak wujud kointegrasi yang signifikan di antara belanja kerajaan agregat dengan output dalam jangka panjang, yang mencerminkan kepentingan peranan sektor swasta dalam merangsang program pembangunan negara.